Islamic Educational Values in Naqsyabandiyah Thoriqot Jabal Kubis - Damanik, Muhammad Zein; Mukti, Abd; Arsyad, Junaidi (LP. Ma'arif Janggan Magetan, 2024)
This study investigates Thoriqot Naqsyabandiyah Jabal Kubis in Batu Bara, Indonesia, and current Islamic education. It addresses the shortcomings of modern education that prioritizes cognitive accomplishment over faith, ethics, and spirituality. The study examines how the thoriqot promotes morality and character development as a non-formal educational institution. In-depth interviews with congregants, firsthand observation of suluk ceremonies, and thoriqot documentation were used to obtain descriptive qualitative data. The findings show three educational dimensions: faith reinforcement through zikir and wirid, worship discipline through communal prayers, sunnah fasting, and suluk training, and moral development through humility, patience, and ukhuwah with mursyid guidance. These findings show that thoriqot institutionalizes spiritual activities as systematic education, transcending its status as a Sufi ritual tradition. Unlike previous studies that focused on Sufism's theology or history, this study emphasizes thoriqot's educational roles as an alternative character education paradigm. The study confirms its significance to national education goals, particularly in developing faith, piety, and noble values and building resilience to modern social issues. Thus, Thoriqot Naqsyabandiyah Jabal Kubis contributes uniquely to Islamic education studies by showing how regional Sufi traditions can be contextualized into a holistic character education model for modern society.